Mensuração de perdas produtivas em frangos de corte devido a variações de temperatura, umidade e altitude no Rio Grande do Sul - Karkow, Ana Kátia (2015)
Along the Brazilian poultry production history, large volumes of data are generate by computational tools or manually collected on production environment. This data may be have implicit patterns, from which is possible to extract new answers to questions that can enhance the production scale. In this sense, this work was developed with a database from Languiru Cooperative of Teutônia, Rio Grande do Sul. Were evaluating lots of 112 associated producers in a five years period, from 2007 to 2012, a total of 2319 observations, and the broiler farms are located in different regions of cooperative scope. Data were tabulated and subsequently submitted to multiple regression analysis, comparison of means and data mining process. The results show that the environmental conditions and the altitude influence broiler production, changing the mortality and weight gain, it nas possible establish mortality and weight gain regression models, involving altitude and environmental variables.